The Urgency of Classical Hakam's Substantive Competence for Mediators in Syiqaq Cases - Navila Ash Shofwa Kamila Farid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article examines the urgency of substantive competence possessed by the classical concept of hakam as a freame of reference for mediators handling syiqaq cases in Indonesian Religious Courts (Pengadilan Agama). Syiqaq a form of severe and on going marital discor, is addressed in fiqh through the appoinment of two arbitrators (hakam) who are expected to be knowledgeable in Islamic family law, trusted by both parties, and ideally drawn from their respective families. However, positive Indonesian law, specifically Article 76 of Law No. 7 of 1989 on Religious Courts, merely allows the court to appoint hakam without prescribing substantive qualification standards. Meanwhile, the mediation procedure under Supreme Court Regulation (PERMA) No. 1 of 2016 only requires a certified mediator without mandating any specialization in Islamic family matters. This normative-doctrinal study, supported by a statutory and conceptual approach, finds that the gap between the classical hakam qualification and the current regulatory framework results in a suboptimal peace-seeking process in syiqaq cases. The novelty of this article lies in its proposal for integrating classical hakam qualification criteria into the certification standard for mediators assigned to syiqaq cases at the Religious Court level, as a concrete reform measure.